Improving Traffic Incident Management Using Intelligent Transportation Systems, A Case of Amman City - et. al., Wala’a Al-Khrisat, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The constant growth of urbanization, and the rising number of vehicle ownership, are affecting urban traffic and making accidents take place recurrently, resulting in traffic jamming, decreasing the efficiency of road network functions, and losses to the community economy. It is necessary to develop and utilize the tools of ITS like adding smart Roads-side unite (RSUs), smart sensors and Variable message signs (V.M.S) and their application to improved incidents management. In order to address this issue, a specific corridor was chosen as a study area, and all related necessary data was collected from governmental authorities, including traffic volumes and accident coordinates. A detailed analysis, and evaluation of the current situation was implemented, and case modeling were made using micro-simulation software VISSIM.10. This study presents eight multiple scenarios for traffic accidents, and improved strategies for managing traffic accidents using smart transportation tools. The results proved the effectiveness of these strategies in improving and raising the level of service on the selected corridor.